Energy Crisis and Nepal’s Potentiality - Upadhaya, Suraj (The Initiation, 2010)
Energy that is not popularly used and is usually environmentally sound like wind, solar, geothermal is simply regarded as renewable energy. The renewable energy made available through established sources and technology is considered as non-conventional one, if otherwise, conventional. Speaking strictly the forms of alternative energy or renewable energy are environmentally favorable and no negative impacts and economically viable. Alternative energy sources are necessary to explored in context to solve the present problem of energy crisis in Nepal. Being rich in natural resources Nepal posses' high potential of development of energy generation station. Key Words: Energy crisis, Hydropower, Alternate energy, Consumption DOI: 10.3126/init.v2i1.2534 The Initiation Vol.2(1) 2008 pp130-135